Prevalence of Symptoms Related to Temporomandibular Disorders in Costa Rica - Cervantes-Chavarría, Andrés (2026)
To determine the prevalence of temporomandibular disorders symptoms in Costa Rican adults during the year 2024. The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) and triage were applied to a convenience sample consisting of 80 people per state (n=400). Data were collected from five of the seven states of the country: San José, Alajuela, Cartago, Heredia, and Limón. Adult patients aged 18-75 years were included. Of those surveyed, 64.9% reported experiencing some type of pain in the jaw, temple, or ear, 42.7% had headaches, 64.7% reported joint noises, 21% had closed mandibular blocks, and 7.2% had open blocks in the jaws within the last 30 days. The symptoms, according to sex, were more prevalent in women and according to the state, Heredia and San José report more patients with symptoms. In the examined Costa Rican sample, there is a high prevalence of symptoms of temporomandibular disorders, with pain and headaches being the most common. Women, residents of the states of Heredia and San José, and individuals aged 26-35 and 46-60 years showed a higher prevalence of symptoms. The instrument showed moderate reliability, suggesting the need for its combined use with a temporomandibular clinical examination in future research.